Ecological restoration projects enhanced terrestrial carbon sequestration in the karst region of Southwest China - Lv, Yan; Zhang, Li; Li, Pan; He, Honglin; Ren, Xiaoli; Zhang, Mengyu (Frontiers in Ecology and Evolution, 2023)
The karst region of southwest China showed a significant increase in vegetation cover and vegetation carbon stocks under the implementation of a series of ecological restoration projects. However, the relative contribution of ecological restoration projects to terrestrial carbon sequestration in the context of climate change has yet to be well quantified. Here, we used the Community Land Model (CLM4.5) to investigate the trend of net ecosystem productivity (NEP) and attribution to multiple environmental factors in the karst region of southwest China during 2000-2018. The result showed that ecosystems with a significant increasing trend of NEP covered about 46% of the study region, which were mainly located in the peak forest plain region, colliculus region, peak cluster depression region, and middle-high hill region. The simulation experiments suggested that land use change associated with ecological restoration projects caused a large contribution of 53% to the increasing NEP trend, followed by CO2 fertilization (72%), while climate factors and nitrogen deposition showed minor negative effects. Especially, the NEP trend induced by land use change in the 100 pilot counties with the implementation of rocky desertification control project was significantly higher than that in the other karst area. Moreover, moderate and high levels of restoration efforts invested into recovery led to a larger increasing trend (0.66 gC/m2/yr2 and 0.48 gC/m2/yr2) in NEP than the low efforts level (0.22 gC/m2/yr2). Our results highlight the important role of ecological restoration projects in the enhanced terrestrial carbon sequestration in the karst region of southwest China, and recommend a comprehensive assessment of ecological restoration projects for policymaking.